Analysis Of Nutritional Status and Vo2Max Volleyball Players Unmus UKM Club - Hendra Jondry Hiskya; Dilli Dwi Kuswoyo; Emanuel Lewar (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2023)
The quality of strength, endurance, flexibility, speed, agility, and good movement coordination. The human body gets nutrients in the form of animal protein and vegetable protein. One type of food alone cannot meet all the needs of the body for various nutrients. According to its function, we can classify nutrients into three, namely energy substances, which consist of carbohydrates, fats and proteins. The anaerobic energy system is divided into alactic anaerobic (phosphagen system, without producing lactate) and lactic anaerobic (lactat system, producing lactate). The alactic anaerobic system provides the ready-to-use energy needed to initiate high-intensity physical activity. The source of energy is obtained from the breakdown of ATP and PC stores available in the muscles. At maximum activity, this system can only be maintained for 6-8 seconds because ATP and PC stores are very small, every 1 kg of muscle contains 4-6 mM ATP and 15-17 mM PC. 1 Mole = 1000 mM equates to 7-12 calories. The results of the Multistage Fitness test study on the UKM Unmus volleyball team had the largest VO2max value of 51.82 and the smallest 34.18. The team's average (mean) VO2 max was 41.70 ml/kg/min and was included in the unfavorable category. While the percentage of body mass index (BMI) test results for volleyball players at UKM Unmus, which consists of 18 players, is normals.